A Flexible, Incentivized Budgeting System for Academic Departments - N. Douglas Lees (Academic Chairpersons Conference Proceedings, 2017)
This session will involve a discussion of the budgeting models of the attendees and a discussion of their overall needs for budgeting guidance. An overview of Responsibility Centered Management (RCM) will be provided along with the model used to set budgets for departments in a School of Science.
Keywords: RCM; budget model; budget formula; flexible dollars; incentivized